Productivity Hot Spots and Cold Spots: Setting Geographic Priorities for Achieving Food Production Targets - Mamiit, Rusyan Jill; Yanagida, John; Miura, Tomoaki (Frontiers in Sustainable Food Systems, 2021)
Rice is the most important staple food in the Philippines as it provides almost half of the calorie requirements of the population. The domestic supply of rice, however, is inadequate to meet local demand, making the Philippines one of the top five rice-importing countries in the world. To close the domestic supply-and-demand gap, agricultural planners and policymakers in the Philippines have been promoting interventions to increase farm-level productivity. In support of the government efforts to increase rice productivity, a stochastic frontier analysis combined with an optimized spatial hot spot analysis was conducted to determine the factors that may influence the increase in rice farm efficiency and also identify candidate areas for relevant geographic-specific rice production interventions. Results show that enhancing access to irrigation and farm inputs and increasing the producers’ technical capacity can help address the local supply deficiency by potentially increasing yield per hectare to as high as 5.50 metric tons per hectare. The approach to potentially increase rice farm technical efficiency and productivity must consider the spatial nature of rice production as suggested by the findings from the optimized hot spot analysis. It is important that policy interventions consider areas with a high incidence of low levels of productivity and technical efficiency. These are the locations where agricultural planners and policymakers can make greater impacts on rice yields. Relevant policies and initiatives, therefore, should take into account the geographical location of farms to ensure the greatest contribution to attaining food production targets.